2011
DOI: 10.1088/0953-2048/24/6/065012
|View full text |Cite
|
Sign up to set email alerts
|

A novel numerical mechanical model for the stress–strain distribution in superconducting cable-in-conduit conductors

Abstract: Besides the temperature and magnetic field, the strain and stress state of the superconducting Nb3Sn wires in multi-stage twisted cable-in-conduit conductors (CICCs), as applied in ITER or high field magnets, strongly influence their transport properties. For an accurate quantitative prediction of the performance and a proper understanding of the underlying phenomena, a detailed analysis of the strain distribution along all individual wires is required. For this, the thermal contraction of the different compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…It appears up to now that for simulation of the evolution of the coupling loss with cycling in the press, a deviation can occur of about a factor of two at high bumber of cycles. It is demonstrated that the amount of critical current degradation from transverse load [60], [61] is subject to interference due to different sub-cable twist pitches, we expect a similar behavior for coupling loss. This opens scope for optimisation of the twist pitch sequence for CICCs to minimise the transverse load degradation, the warm-up cool-down degradation and the coupling loss.…”
Section: Figure 12 a Validation Of The Jackpot-acdc Model Based On Tmentioning
confidence: 65%
“…It appears up to now that for simulation of the evolution of the coupling loss with cycling in the press, a deviation can occur of about a factor of two at high bumber of cycles. It is demonstrated that the amount of critical current degradation from transverse load [60], [61] is subject to interference due to different sub-cable twist pitches, we expect a similar behavior for coupling loss. This opens scope for optimisation of the twist pitch sequence for CICCs to minimise the transverse load degradation, the warm-up cool-down degradation and the coupling loss.…”
Section: Figure 12 a Validation Of The Jackpot-acdc Model Based On Tmentioning
confidence: 65%
“…Several models [8]- [10] have been introduced to analyze the cable pattern for Nb3Sn or NbTi CICC, including cabling and conductor operation at low temperature. Large tension on strands and cable can cause undesired single strand elongation or damage during cabling.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the results are reported of investigations on a cable made of three single Bi2212 round wires with different pitches subjected to tensile stress-strain tests at 300 K. The mechanical properties were analyzed by a numerical cable model [10]. The experimental results were compared to the numerical model for conditions at 300 K. Then the model was used to analyze the strain distribution of a single wire in different cable configurations at room and cryogenic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigation on local stress and strain distribution map is insufficient [16]. Besides, Qin et al [17,18] develop a theoretical mechanical model (CORD) for a superconducting cable based on wire rope theory. CORD can predict the local strain and stress state of all individual wires, including inter-strand contact force and the associated deformation.…”
Section: Introductionmentioning
confidence: 99%